Alleviation of the effect of salinity on pomegranate seedlings by priming foliar spray of chitosan-silicon nanoparticles (CTS-SiO2 NPs) - Mohammadi, Zeinab; Zahedi, Seyed Morteza; Panahirad, Sima; Gohari, Gholamreza (My University, 2025)
Today, improving the nutritional status of plants using external supplements, particularly based on nanotechnology, is of great importance to compensate for the damage caused by abiotic stresses. Salinity is one of the chief environmental stresses limiting the growth and yield of crops by reducing the osmotic potential and disrupting the absorption of water and nutrients. The present study was conducted to compare the priming effect of foliar spraying the following treatments: silicon nanoparticles (SiO2 NPs; 50 mg L-1), chitosan nanoparticles (CTS NPs; 0.1%), chitosan-silicon nanoparticles (CTS-SiO2 NPs; 25 and 50 mg L-1) and distilled water (control). These treatments were assayed on reducing the effects of sodium chloride (NaCl) salinity stress (0 and 150 mM) on two-year old pomegranate seedlings.
Keywords: Nanotechnology; Osmolyte; Oxidative stress; Plants; Salinity